A political-constitutional conflict in times of war. Reflections on an unpublished text by Jovellanos Un conflicto político-constitucional en tiempos de guerra. Reflexiones a la luz de un escrito inédito de Jovellanos - Ignacio FERNÁNDEZ SARASOLA (Cuadernos Dieciochistas)
In May 1809, Pedro Caro y Sureda, Marqués de la Romana, dissolved the Junta Superior de Asturias. This assembly had been created from an ancient institution (Junta General del Principado de Asturias), and it was, in fact, the first revolutionary assembly in Spain to declare war to Napoleon. Jovellanos had been elected by the same assembly to become a part of the Junta Central, and he was against the dissolution of the Junta of Asturias. This was the origin of an important political conflict between Jovellanos and La Romana, which reached the Junta Central and the Consejo de Castilla as well. En mayo de 1809, Pedro Caro y Sureda, Marqués de la Romana, disolvió la Junta Superior de Asturias. Dicha asamblea había sido creada a partir de una antigua institución (la Junta General del Principado de Asturias) y, además, había sido la primera asamblea revolucionaria española en declarar la guerra a Napoleón. Jovellanos había sido elegido por dicho órgano para formar parte de la Junta Central y se opuso a la disolución de la Junta de Asturias. Ese fue el origen de un importante conflicto político entre Jovellanos y La Romana, que alcanzó a la Junta Central y al Consejo de Castilla.